Big Data Analytics Third International Conference, BDA 2014, New Delhi, India, December 20-23, 2014. Proceedings - Srinivasa, Srinath; Mehta, Sameep; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed conference proceedings of the Third International Conference on Big Data Analytics, BDA 2014, held in New Delhi, India, in December 2014. The 11 revised full papers and 6 short papers were carefully reviewed and selected from 35 submissions and cover topics on media analytics; geospatial big data; semantics and data models; search and retrieval; graphics and visualization; application-specific big data.
Media analytics -- Geospatial big data -- Semantics and data models -- Search and retrieval -- Graphics and visualization -- Application-specific big data.
Keywords: Computer science; Algorithms; Database management; Data mining; Information storage and retrieval; Computer Science; Data Mining and Knowledge Discovery; Database Management; Information Storage and Retrieval; Algorithm Analysis and Problem Complexity; Electronic books